PENGARUH TEKNIK AFIRMASI TERHADAP TINGKAT STRESS KERJA PERAWAT COVID-19 - Jaya KK, Indra Frana; Irfannuddin, Irfannuddin; Santoso, Budi (JURNAL MEDIA KESEHATAN, 2020)
At the end of 2019, the world was shocked by the outbreak of a new pneumonia that started in Wuhan, Hubei Province which then spread rapidly to more than 190 countries and territories. This outbreak is named coronavirus disease 2019. The first Covid-19 was reported in Indonesia on March 2, 2020, and March 31, 2020 data shows that there were 1,528 confirmed cases. This pandemic resulted in an increasing number of infected patients and resulted in the need for more intensive nurses and especially in hospitals. Nurses are the health workers who most interact with Covid-19 patients when they are treated at the hospital, this can result in stress related to this situation that has never been experienced at all in Indonesia. Affirmation is a therapy that can be used to reduce the stress level of a nurse's job. The purpose of this study was to see the effect of affirmation techniques on the work stress level of Covid-19 nurses. The design used in this study was quasi-experimental with pre and post test. Data analysis used t-test. The sampling technique in this study was total sampling, the number of samples in this study was 25 respondents, the study was conducted by giving a nurse work stress questionnaire (ENSS) before and after the intervention with affirmation techniques, the intervention was carried out 4 times a week for 4 weeks. The average level of work stress before the intervention was 119.24 with a maximum value of 160 and a minimum value of 93. The average level of work stress after intervention was 92.92 with a maximum value of 120 and a minimum value of 65, from the data. The results of the statistical test of the work stress level of Covid-19 nurses before and after the intervention with affirmation techniques obtained p-value = 0,000. The implication of this research is expected to be applied continuously to maintain the mental health of nurses and to care for Covid-19 patients